The association between living altitude and serum leptin concentrations in native women - Cheng, Jiayu; Luo, Yingying; Yang, Lihui; Li, Yufeng; Zhang, Fang; Zhang, Xiuying; Zhou, Xianghai; Ji, Linong (Frontiers in Endocrinology, 2023)
Background: Lower diabetes prevalence and cardiovascular mortality have been observed in residents at a higher altitude. Leptin is associated with incident diabetes and adverse cardiovascular outcomes, and our aim was to investigate the association of living altitude with serum leptin concentrations. Methods: Two cross-sectional surveys were used in this study, including native populations living at Tibet (high altitude) and Beijing (low altitude). A propensity score was conducted for matching age and body mass index (BMI) between native women at high and low altitude. Pearson’s correlation analysis was performed to evaluate the correlation of leptin with other variables. Results: A total of 1414 native women were included in this study, including 594 at high altitude and 820 at low altitude. The serum leptin concentrations of native women living at high altitude were 13.74 ± 11.03 ng/ml, which was significantly lower than that of native women living at low altitude (20.90±12.91 ng/ml). After matching age and BMI, women living at the high altitude still had lower serum leptin concentrations. After adjusting for the potential confounding factors, the correlation coefficient between Ln (leptin) and BMI of women at high altitude was significantly lower than that of women at low altitude (0.228 versus 0.559; P <0.0001). The serum leptin concentrations of each BMI subgroup (<18.5, 18.5 to <25, 25 to <30, ≥ 30 kg/m2) in women at high altitude were lower than that in women at low altitude. Conclusions: Serum leptin concentrations were significantly decreased in native women living at high altitude, and living altitude may alter the correlation of BMI and leptin. The findings of our study support that residents at high altitude have a protective effect with regards to improving cardiovascular and metabolic outcomes.